Teaching in Rural Areas: Voices of Surviving Civil Servant Teachers of English - Khotimah, Arria; Mirizon, Soni; Silvhiany, Sary (Universitas Jambi, Indonesia, 2024)
In the 3T, Tertinggal, Terluar, Terdepan (Lagging, Outermost, and Frontier) areas, many obstacles and difficulties are faced by educators in Indonesia concerning human resources, infrastructure, and the environment. This study aims to explore how civil servant teachers of English survive teaching in the 3T areas. This study uses a phenomenological design. The data were collected using observation and interview. Three civil servant teachers of English who commuted regularly from the city to the rural area were involved as the participated in this study. Four key themes emerged as findings: teacher motivation, professional development, survival in teaching, and teaching experiences. Teacher motivation was related to their reasons to retain teaching in rural areas. Professional development covered teacher training, further study. Survival teaching included challenges teachers of English encountered, strategies applied, and solutions taken. Teaching experiences covered their opportunity to use more than one language, community bound, and culture adjustment. These elements are critical to fostering a sustainable and impactful educational environment in rural communities.